(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
Islam has a political concept that functions to realize synergistic welfare between the interests of the world and the hereafter. In Islam, the government must take a significant role in regulating people’s lives based on the principles of the Qur’an and Sunnah. In the Indonesian context, regional autonomy provides wider space for regions to develop their territories so that people’s welfare can be realized. Various studies show that local governments play a major role in efforts to improve people’s welfare through their development policies. Jambi Province is a region that has held several regional elections, one of which was in 2015 when Zumi Zola and Fachrori Umar were elected as governor and deputy governor. Efforts to build Jambi with its various resources are carried out by the government through its vision and mission known as TUNTAS and aimed at improving the welfare of the community in 2015-2021. Based on this research, it is known that poverty is still a major problem that must be resolved by the Jambi Provincial Government. In addition, unemployment and development inequality between regions in Jambi Province are also problems that the government should pay attention to through innovative-solution policies in the future. Islam memiliki konsep politik yang berfungsi untuk merealisasikan kesejahteraan yang sinergis antara kepentingan kehidupan dunia dan akhirat. Pemerintah dalam Islam harus mengambil peran yang signifikan dalam mengatur kehidupan masyarakat berdasarkan prinsip-prinsip al-Qur‟an dan Sunnah. Dalam konteks Indonesia, otonomi daerah memberi ruang yang lebih luas bagi daerah untuk membangun wilayahnya agar kesejahteraan masyarakat dapat terwujud. Upaya membangun diwujudkan melalui kebijakan-kebijakan pembangunan pemerintah daerah yang diusung kepala daerah yang terpilih melalui pilkada. Beragam studi memperlihatkan bahwa pemerintah daerah berperan besar dalam upaya meningkatkan kesejahteraan masyarakat melalui kebijakan-kebijakan pembangunannya. Provinsi Jambi merupakan wilayah yang telah beberapa kali menyelenggarakan pilkada, salah satunya tahun 2015 dengan terpilihnya Zumi Zola dan Fachrori Umar sebagai gubernur dan wakil gubernur. Upaya membangun Jambi dengan beragam sumberdayanya dilakukan pemerintah melalui visi misinya yang dikenal dengan TUNTAS dan ditujukan untuk meningkatkan kesejahteraan masyarakat tahun 2015-2021. Berdasarkan penelitian ini diketahui bahwa kemiskinan masih menjadi problem utama yang harus dicarikan solusinya oleh Pemerintah Provinsi Jambi. Di samping itu, pengangguran dan ketimpangan pembangunan antar wilayah di Provinsi Jambi juga menjadi problem-problem yang harus menjadi perhatian pemerintah melalui kebijakan-kebijakan inovatif-solutif di masa-masa mendatang.